2015
DOI: 10.1007/s00436-015-4637-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of allicin on chicken Eimeria tenella sporozoites

Abstract: Chicken coccidiosis is a major parasitic disease caused by Eimeria spp. It is controlled and treated using chemical anticoccidial agents. Development of partial or complete resistance toward these anticoccidials is considered a major problem in poultry industry. Allicin is an organosulfur compound produced as a result of the reaction between alliin and alliinase after hacking of garlic. In this study, tenfold dilution from 180 mg/ml to 1.8 ng/ml of allicin in distilled water was tested against E. tenella in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Garlic and its sulfur compounds, allicin, alliin, ajoene, diallyl sulfide, dithiin, and allylcysteine, are reported to have broad antimicrobial activities which can eliminate negative factors of microbial infections. An in vitro study has shown that allicin inhibits sporulation of E. tenella effectively [ 26 – 28 ]. The anticoccidial mechanism of garlic and its sulfur compounds remains elusive.…”
Section: Plants and Compounds For Avian Coccidiosismentioning
confidence: 99%
“…Garlic and its sulfur compounds, allicin, alliin, ajoene, diallyl sulfide, dithiin, and allylcysteine, are reported to have broad antimicrobial activities which can eliminate negative factors of microbial infections. An in vitro study has shown that allicin inhibits sporulation of E. tenella effectively [ 26 – 28 ]. The anticoccidial mechanism of garlic and its sulfur compounds remains elusive.…”
Section: Plants and Compounds For Avian Coccidiosismentioning
confidence: 99%
“…The crude product was purified by flash column chromatography on silica gel using hexanes/EtOAc (90:10) as eluent. This compound was obtained as yellow needles in 74% yield, mp 160-161 °C; IR (KBr) n / cm - General procedure for the preparation of 1,4-dioxo-3-aryl-1,4-dihydronaphthalen-2-yl diethylcarbamates (7a-e) and 3-(3-methylbut-2-en-1-yl)-1,4-dioxo-1,4-dihydronaphthalen-2-yl diethylcarbamate (8) A stirred solution of 1 (0.1 mmol) or 4 (0.1 mmol), pyridine (5 equiv), N,N-diethylcarbamoyl chloride (20 equiv), in CHCl 3 (10 mL) was heated at 60 °C for 18 hours. Dichloromethane (30 mL) was added to the reaction mixture and the organic layer was first washed with a solution of hydrochloric acid 1N (30 mL) and then with brine (3 × 30 mL), dried over anhydrous Na 2 SO 4 and concentrated in vacuo.…”
Section: General Procedures For the Preparation Of 2-methoxy-3-iodonapmentioning
confidence: 99%
“…Eiremia tenella is a protozoan disease that causes poultry coccidiosis impacting directly in chicken industry and global food supply due to the high mortability. 8 Lapachol (1) has been used as starting point to obtain new bioactive quinones showing interesting pharmacological profiles. 9,10 Herein, we would like to report the synthesis of 2-hydroxy-3-arylnaphthalene-1,4-diones, analogues of WS-5995-C that can also be considered analogues of 1 in which the prenyl side chain is substituted by an aromatic ring ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic and its sulfur compounds, i.e., allicin, alliin, ajoene, diallyl sulfide, dithiin, and allylcysteine, are reported to have broad antimicrobial activities. An in vitro study has shown that allicin inhibits sporulation of E. tenella effectively [ 30 ]. Green tea extracts significantly inhibited the sporulation process of coccidian oocysts.…”
Section: Discussionmentioning
confidence: 99%